Preparation of photoluminescence tunable Cu-doped AgInS2 and AgInS2/ZnS nanocrystals and their application as cellular imaging probes. Issue 56 (25th May 2016) - Chen, Siqi; Demillo, Violeta; Lu, Minggen; Zhu, Xiaoshan
Abstract : Photoluminescence tunable Cu-doped AgInS2 and AgInS2 /ZnS nanocrystals were synthesized and applied in cellular imaging. Abstract : In this work, high-quality Cu doped AIS and AIS/ZnS NCs have been first synthesized via a surface doping approach. By varying the Cu doping concentrations, Cu doped AIS NCs exhibit a photoluminescence red-shift from around 600 nm to 660 nm with a decrease of quantum yield from around 30% to 20%. After ZnS coating or zinc etching on the Cu doped AIS NCs, Cu doped AIS/ZnS NCs present photoluminescence peaks from around 570 nm to 610 nm and high quantum yields in the range of 50–60%. Moreover, it is found that Cu doping can prolong the photoluminescence lifetime of NCs, and the average photoluminescence lifetime of Cu doped AIS and AIS/ZnS NCs is in the range of 300–500 ns. The resultant Cu doped AIS/ZnS NCs were further encapsulated with amphiphilic polymers and used as biocompatible photoluminescence probes in cellular imaging. The cellular imaging study shows that peptide-conjugated probes can specifically target U-87 brain tumor cells and thus they can be applied to the detection of endogenous targets expressed on brain tumor cells.